Trade and Migration to New Zealand - John Bryant; Murat Genç; David Law (European Regional Science Association (ERSA), 2005)
This paper examines the hypothesis that a greater stock of migrants in New Zealand from a particular country leads to more trade between that country and New Zealand. The literature suggests that migrants can stimulate trade by lowering transaction costs, and by bringing with them preferences for goods produced in their home country. We use panel data techniques within the framework of a standard gravity model of trade. Our sample includes an average of over 170 countries for the years 1981 to 2001. Previous studies of trade and migration have not dealt satisfactorily with problems of unobserved heterogeneity and selection bias. We address these problems using correlated random effects and selection models. Results suggest that larger migrant stocks are associated with higher trade flows.
Keywords: 330